Exploring Talent Retention Strategies in Local Government Institutions of Makassar: A Phenomenological Study - Dipoatmodjo, Tenri Sayu Puspitaningsih (Abadi Institute, 2025)
This phenomenological study examines the lived experiences of talent retention strategies within Makassar's local government institutions, exploring how cultural values, organizational climate, and leadership styles influence employee commitment in the Indonesian public sector context. Through in-depth interviews with 15 participants comprising HR managers and employees across various government departments, the research investigates the subjective meanings and experiences that shape talent retention decisions. Using Colaizzi's seven-step phenomenological analysis framework, the study identified five essential themes: Cultural Harmony and Collective Belonging, Leadership Authenticity and Emotional Connection, Professional Growth Within Bureaucratic Constraints, Work-Life Integration and Family Values, and Service Purpose and Community Impact. The findings reveal that talent retention in Makassar's local government is fundamentally shaped by the integration of traditional Bugis-Makassar cultural principles—sipakatau (mutual respect), sipakalebbi (mutual honoring), and sipakainge (mutual remembrance)—with contemporary organizational practices. Participants emphasized the significance of authentic leadership characterized by